The Unequal Benefits of Fuel Subsidies : A Review of Evidence for Developing Countries - Coady, David (IMF Working Papers; Working Paper, 2010)
This paper reviews evidence on the impact of fuel subsidy reform on household welfare in developing countries. On average, the burden of subsidy reform is neutrally distributed across income groups; a USD 0.25 decrease in the per liter subsidy results in a 6 percent decrease in income for all groups. More than half of this impact arises from the indirect impact on prices of other goods and services consumed by households. Fuel subsidies are a costly approach to protecting the poor due to substantial benefit leakage to higher income groups. In absolute terms, the top income quintile captures six times more in subsidies than the bottom. Issues that need to be addressed when undertaking subsidy reform are also discussed, including the need for a new approach to fuel pricing in many countries.